A simple and inexpensive point‐of‐care test for hepatitis B surface antigen detection: serological and molecular evaluation. Issue 12 (30th April 2014) - Gish, R. G.; Gutierrez, J. A.; Navarro‐Cazarez, N.; Giang, K.; Adler, D.; Tran, B.; Locarnini, S.; Hammond, R.; Bowden, S.
Summary Early identification of chronic hepatitis B is important for optimal disease management and prevention of transmission. Cost and lack of access to commercial hepatitis B surface antigen (HBsAg) immunoassays can compromise the effectiveness of HBV screening in resource‐limited settings and among marginalized populations. High‐quality point‐of‐care (POC) testing may improve HBV diagnosis in these situations. Currently available POC HBsAg assays are often limited in sensitivity. We evaluated the NanoSign® HBs POC chromatographic immunoassay for its ability to detect HBsAg of different genotypes and with substitutions in the 'a' determinant. Thirty‐seven serum samples from patients with HBV infection, covering HBV genotypes A–G, were assessed for HBsAg titre with the Roche Elecsys HBsAg II quantification assay and with the POC assay. The POC assay reliably detected HBsAg at a concentration of at least 50 IU/mL for all genotypes, and at lower concentrations for some genotypes. Eight samples with substitutions in the HBV 'a' determinant were reliably detected after a 1/100 dilution. The POC strips were used to screen serum samples from 297 individuals at risk for HBV in local clinical settings (health fairs and outreach events) in parallel with commercial laboratory HBsAg testing (Quest Diagnostics EIA). POC testing was 73.7% sensitive and 97.8% specific for detection of HBsAg. Although the POC test demonstrated high sensitivity over a range of genotypes, false negatives were frequent in a clinical setting. Nevertheless, the POC assay offers advantages for testing in both developed and resource‐limited countries due to its low cost (0.50) and immediately available results.